Changes of general & physical characters of sheep wool in Induce copper deficiency in Awassi sheep: Jinan Ali Khalidi , Saadi Ahmmed Ghanawi , Laila Muhammad Zaki - Khalidi, Jinan Ali (The Iraqi Journal of Veterinary Medicine, 2006)
To induce copper deficiency in sheep 15 Awassi ewes were choosen from theveterenary medicine collage and randomly divided into three equal groups for theexperimental period (18 weeks).the 1st group were fed on balanced concentrated diet with low level of copper(2.6) mg/day was used to feed the primary deficiency group while the 2nd groupwere fed on a balanced concentrated diet contained 5.2 mg/day copper in additionof the green food and the protein ratio and energy level were considered. Thesecondary deficiency group received an oral mixture of ammonium molybdate100 mg with 1 g of sodium sulphate in 100 ml of water daily.Wool samples from the ewes and their lambs were collected to study thehanges in wool physical traitsThe experimental ewes were treated in two different ways. The primarydeficiency group fed on balanced concentrated diet contained high level ofcopper (7.4) mg/day, while the secondary deficiency group treated orally withcopper sulphate (1.5) g/ewe/day dissolved in water for (6 weeks). After twoweeks of treatment the parameters raised and the ewes in the two groups lookedmore healthy, the wool start to grow and by the end of that period all symptomsand changes return to normal in comparison with the control group